ANALISIS KESALAHAN SISWA SMK DALAM MENYELESAIKAN SOAL MATERI MATRIKS - Wardhani, Irma Kusuma; Chotimah, Siti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The focus of this research is to find out students' mistakes when solving matrix material problems. The subjects in this study were class X students in one of the private vocational schools in Kab. Bandung with a total of 23 people. The research method used is descriptive qualitative research. In this study there are three stages, namely planning, implementation, and reporting. This research data collection, using student test results based on a matrix question instrument in the form of a description consisting of five questions. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The conclusion in this study there are errors made by students when answering the questions that have been given, namely: students do not use matrix symbols, students do not work systematically, students are still wrong in calculating the final results, students do not carry out the calculation process, students do not understand the problem, students do not find conclusions, the problem solving is not to the end. The percentage of student errors with the highest criteria in solving matrix material questions is in question number 5 with a percentage of 92%. Meanwhile, the student's error with the lowest criteria is in question number 1 with a percentage of 16%.